Self-organising of Atoms in Germanium and Silicon Melts - E.J. Shvetz; I.F. Chervony; O.K. Golovko (Журнал нано- та електронної фізики)
Propensity of germanium and silicon atoms to self-organizing in melts with formation microclasters in the form of chains with covalent internuclear communications is proved. It is developed distributions model in the sizes of microclasters. By means of model are estimated as much as possible probable and average quantity of atoms in microclaster depending on temperature. At melting temperature in germanium melt average quantity of atoms in chain Aver = 2,60, and their as much as possible probable quantity – ≈ 1. Accordingly, in silicon melt – Aver = 2,77, and as much as possible probable quantity of atoms – ≈ 2. At boiling temperature in both melts the maximum density of probabilities answers individual atoms. Results of estimations well coordinated with experimental data from the literature. Work pursues the aim of deepening of representations about processes of self-organising and structural reorganisation in melts elementary semiconductors which influence on crystallization mechanism.